Review of recent developments in ultra-high field (UHF) NMR magnets in the Asia region. (1st April 2022) - Yanagisawa, Y; Hamada, M; Hashi, K; Maeda, H
Abstract: This paper reviews recent developments in ultra-high field (UHF) superconducting magnets for nuclear magnetic resonance (NMR) in the Asia regionin particular, those for high-resolution NMR magnets using high-temperature superconductor (HTS) coils. In Japan, a power supply driven-mode 1.02 GHz (24.0 T) NMR magnet using a Bi2 Sr2 Ca2 Cu3 O10- δ (Bi-2223) inner coil was developed in 2015, providing the first high-resolution NMR at a 1 H NMR frequency of >1 GHz (23.5 T). In late 2017, a new project was started to develop a persistent-mode 1.3 GHz (30.5 T) NMR magnet comprising a RE(rare earth)Ba2 Cu3 O7- δ (REBCO) inner coil, a Bi-2223 middle coil, and a low-temperature superconductor (LTS) outer coil. The magnet employs the newly developed state-of-the-art superconducting joints between HTSs necessary for the persistent-mode operation, as well as magnet technologies providing an ultra-high magnetic field of >30.5 T with high temporal stability and spatiality homogeneity for high-resolution NMR measurement. In China, a ∼20 mm cold bored magnet comprising an LTS outer coil and no-insulation (NI) REBCO inner coils was developed and recorded a field of 32.35 T, the highest magnetic field ever achieved with an all-superconducting magnet, which can be used as a small cold-bored NMR. In Korea, a liquid helium-free 400 MHz (9.39 T) all REBCO NMR magnets using NI winding was developed, which is operational. These technologies provide future perspectives for a UHF NMR magnet with key features of persistent-mode operation, an operating field of 1.4 GHz using (32.9 T)-class magnets, and the liquid helium-free operation.